AN ANALYSIS OF THE RELEVANCE OF ENGLISH MATERIALS IN TEXTBOOK ENTITLED “BRIGHT 1” FOR JUNIOR HIGH SCHOOL GRADE VII PUBLISHED BY ERLANGGA TO THE 2013 CURRICULUM (RETAIN, 2015)
ABSTRACT Now a days, government launches 2013 curriculum and changes the last curriculum in many aspects including material. Textbook is one of the material resources, English language teachers use texbook as their main sources of teaching. Therefore, textbook should be matched with curriculum applied. It is difficult to select the best textbook which is suitable with 2013 curriculum to solve this problem, the reseacher focused this study: To describe the relevance of the materials in textbook entitled “Bright 1 for SMP” to the 2013 English Standard Competence in terms of material development andscientific approach. This study was designed in describtive qualitative reseach. The instrument used to collect the data is observation in the form of checlists. After being analyzed, it is found that all chapter are relevant with basic competences of curriculum and learning activities are relevant to scientific approach. After all, the researcher argues that this textbook is appropriate to be used in order to help teacher and students in the process of teaching and learning. Key words: analysis, relevance, materials, textbook, the 2013 Curriculum